Relevance of the Uruguay and Doha Rounds in the evolution of international agricultural trade: The case study of Latin American countries and continental products - Francisco Javier Castellano-Álvarez; Rafael Robina Ramírez (Economies, 2023)
This article describes the evolution of the regulation of agricultural trade and analyses key aspects of the negotiations of the Uruguay and Doha Rounds, in which the least developed countries managed to make the final outcome of the negotiations conditional on progress in the liberalisation of agricultural trade. Four Latin American countries (Argentina, Brazil, Chile and Uruguay) participated in the lobbying groups set up in both Rounds with the aim of defending their interests against the agricultural and protectionist policies of developed countries. Using specialised databases on international trade, this paper describes the consequences of these negotiations for the foreign agricultural trade of the countries that actively participated in them, with particular reference to the evolution of European and Latin American trade balances. The results of the research show how Latin American countries have become one of the world's main exporters of oilseeds and sugar, accounting for a third and a quarter of world exports, respectively. In contrast to the deterioration of the European trade balance, during the period analysed the aggregate trade surplus of Latin American countries increased from USD 4458.75 to 49,656.52 million.
Keywords: 330; agricultural protectionism; CAIRNS; EAMD; EU; export subsidies; USA